Dynamic self-assembly of nanoparticles using thermotropic liquid crystals. Issue 13 (7th December 2016) - Bagiński, Maciej; Szmurło, Anna; Andruszkiewicz, Aneta; Wójcik, Michał; Lewandowski, Wiktor
ABSTRACT: 3D nanoparticle-based materials with reconfigurable structure have gained vast attention due to the unique possibility of tailoring nanoparticle-related quantum confinement effects. These properties make active nanoparticle assemblies promising candidates for future optoelectronic and metamaterial technologies; however, integration of these materials into real-world applications is still challenging. In this context, the use of stimuli responsive liquid-crystals (LCs) offers a fascinating and industrially feasible strategy for active directing of NPs. Here, we briefly review LCs/NPs hybrid systems in which dynamic behaviour is achieved by affecting either LC matrix or LC ligands. We also experimentally evaluate a complementary strategy based on directly affecting metallic core of LC-covered NPs in an Ostwald ripening process. GRAPHICAL ABSTRACT: